2019
DOI: 10.1111/ajps.12458
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Debates on Political Attitudes

Abstract: for their collaboration and facilitation of the project. We thank Samuel Kweku Yamoah for helping us to field the survey. We are also grateful to the team of research enumerators who conducted the surveys. Miguel Pereira provided excellent research assistance. Thanks to Darin Christensen, John Sides, and Lynn Vavreck for their feedback on the research design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…Our work is closest to research by Kendall et al (2015), Bidwell et al (2015), Brierley et al (2018, and Cruz et al (2018). Kendall et al (2015) use a similar structural model to analyze the effects on voter behavior of the distribution of information on a valence issue (candidate competence and effort) and on candidate ideology.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our work is closest to research by Kendall et al (2015), Bidwell et al (2015), Brierley et al (2018, and Cruz et al (2018). Kendall et al (2015) use a similar structural model to analyze the effects on voter behavior of the distribution of information on a valence issue (candidate competence and effort) and on candidate ideology.…”
Section: Introductionsupporting
confidence: 81%
“…We provide information on specific future policy commitments, rather than focusing on a simple left-right ideology scale, and give voters information about the campaign promises of all candidates and not only the incumbent mayors. Bidwell et al (2015) and Brierley et al (2018) expose random voters to candidate debates.…”
Section: Introductionmentioning
confidence: 99%
“…Resnick (2014) and Cheeseman and Larmer (2015) show that opposition candidates have combined ethnic and populist appeals to retain the reliance on charismatic leadership but send a message of common marginalization resonating across ethnic lines. Bleck and Van de Walle (2013, 2019) argue that uncertainty regarding voting allegiances leads politicians to prioritize valence issues in national elections and Brierley et al (2019) add that parties can offer different policy solutions to common valence concerns. Klaus and Paller (2017) show that parties vary in the extent, to which they make inclusive versus exclusive appeals in urban Ghana.…”
Section: Existing Approaches To Cross-ethnic Campaigning In Africamentioning
confidence: 99%
“…A community radio station in each of these rural districts invited 1000 randomly-selected citizens to a public venue to view a screening of the recorded candidate debate for their area and/or participate in small-group discussions about the candidates and issues. 2 Recent randomized studies in Ghana, Sierra Leone, and Uganda, where candidate debates are also relatively novel, have found that exposure to candidate debates (sometimes followed by community discussion) increased voters' knowledge about the candidates and their policies and affected how they voted in some contexts (Bidwell, Casey & Glennerster 2016, Brierley, Kramon & Ofosu 2018, Platas & Raffler 2017. To illustrate our method for DiDiD with placebo outcomes, we assess whether exposure to the candidate debates ahead of these historic elections affected a related but different outcome -citizens' sense of political efficacy.…”
Section: Simulation Studymentioning
confidence: 99%